1975
DOI: 10.1007/bf00348108
|View full text |Cite
|
Sign up to set email alerts
|

A study on the population dynamics of the perennial plant species Chamaenerion angustifolium (L.) scop.

Abstract: From a study of differently aged populations of the perennial plant species Chamaenerion angustifolium a concept was deduced concerning the population dynamics of the species. The age structure was determined by counting the rings of periderm in the roots. After the establishment of seedlings vegetative propagation is the main factor in population development. The longevity of populations depends on exogenic factors, since older root samples-if isolated from the population-appeared to be as viable as were youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…The application of a simple linear transformation by using the presented LDMC ratio as a correction factor resulted in predicted dry weights of A. capillaris, D. flexuosa, D. purpurea, E. angustifolium and R. idaeus that explained 62-93% of the variance of observations. These predictions were consistent with biomass values found by different authors under high light availability for these species (van Andel 1975;Al-Mufti et al 1977;van Baalen and Prins 1983;Fahey et al 1991). Differences in biomass or growth performance under different light regimes have been reported before for D. flexuosa (Scurfield 1954), D. purpurea (van Baalen and Prins 1983), E. angustifolium (Myerscough 1980) and R. idaeus (Ricard and Messier 1996), with all species showing maximum dry weights on open sites.…”
Section: Performance Of Phytocalc On Clearcuts: Dry Weightsupporting
confidence: 91%
See 1 more Smart Citation
“…The application of a simple linear transformation by using the presented LDMC ratio as a correction factor resulted in predicted dry weights of A. capillaris, D. flexuosa, D. purpurea, E. angustifolium and R. idaeus that explained 62-93% of the variance of observations. These predictions were consistent with biomass values found by different authors under high light availability for these species (van Andel 1975;Al-Mufti et al 1977;van Baalen and Prins 1983;Fahey et al 1991). Differences in biomass or growth performance under different light regimes have been reported before for D. flexuosa (Scurfield 1954), D. purpurea (van Baalen and Prins 1983), E. angustifolium (Myerscough 1980) and R. idaeus (Ricard and Messier 1996), with all species showing maximum dry weights on open sites.…”
Section: Performance Of Phytocalc On Clearcuts: Dry Weightsupporting
confidence: 91%
“…K is preferentially stored in flowers and fruits, and not impoverished in stems; however, the leaching of this highly soluble element, due to higher amounts of rainfall reaching the plants on clearcuts, seems to be more important (Höhne 1962;Morton 1977;Larcher 2001). Furthermore, most of these species are growth-limited due to the low light availability under a closed canopy (Scurfield 1954;van Andel 1975;Al-Mufti et al 1977;van Baalen and Prins 1983;Strengbom et al 2004). Thus, under clearcut conditions growth is largely enhanced, although the amount of available nutrients might not increase at the same rate, despite a faster mineralisation after clearcutting.…”
Section: Performance Of Phytocalc On Clearcuts: Dry Weightmentioning
confidence: 99%
“…ERIKSSON (1997) suggested that in species for which seedling recruitment occurs only in the early stages of population development, selection should favour small seed sizes and high fecundity that increase the chance of finding new suitable sites for colonization. Interestingly, in Epilobium angustifolium, a species with an even more pronounced ability to spread laterally ( VAN ANDEL 1975) and belonging to the same section (Charnaenerion TAUSCH) of the genus, the trend for more numerous seeds at the expense of seed mass continues. E. angustifolium has 400-500 ovules per fruit and tiny seeds, three times smaller even than the seeds of E. fleischeri (pers.…”
Section: Trade-off Between Seed Mass and Numbermentioning
confidence: 99%
“…Chemical changes or variations in the nutrient budget strongly influence the mineral status, growth, and reproduction of the plants concerned (e.g. Van Andel 1975;Tolsma et al 1987;Ernst et al 1987;Reekie & Bazzaz 1987;Crick & Grime 1987;Kuiters et al 1987). Plants adapt to these variations in the nutrient status of the soil and life-history parameters change.…”
Section: Discussionmentioning
confidence: 99%
“…Ernst 1981Ernst , 1983Van Andel et al 1984). Further examples of responses at the vegetation level and at the population and species level to changing chemical soil conditions can be found in Van Andel et al (1987). The effects of changing physical conditions on life-history parameters are strongly underestimated in models on plant demography.…”
Section: Discussionmentioning
confidence: 99%